The methods of treatment of atrial fibrillation in patients with valvular heart disease - O.M. Grytsay; Y.V. Skybchyk; I.Y. Mokryk; E.V. Zhytyns’kiy; V.О. Kuts; О.J. Zharinov; B.M. Todurov (Кардіохірургія та інтервенційна кардіологія)
The article presents literature data on the methods of treatment of atrial fibrillation in patients with valvular heart disease. The clinical efficacy of surgical treatment in patients with atrial fibrillation is presented – surgical isolation of the left atrium, «corridor» and Maze procedures. It is emphasized that Maze operation has four modifications, and for today Maze IV is the most common intervention in valvular atrial fibrillation, significantly reducing the risk of thromboembolic complications associated with atrial fibrillation. The efficiency of surgical ablation in valvular atrial fibrillation is discussed, i.e. radiofrequency ablation, laser ablation, microwave ablation, their efficiency in addition to surgical treatment. The article also presents the results of clinical trials in valvular atrial fibrillation, after surgical and complex treatment. It is indicated that a novel metod of treatment in patients with valvular atrial fibrillation is mini-access thoracotomy; after progression of minimally invasive cardiac surgery, modifications of Maze-procedures were performed through a mini-thoracotomy access or thoracoscopy with the usage of endoscopic complex. In conclusion, despite numerous clinical trials, none provided evidence base to determine statistically significant differences in survival; it has not currently been determined how surgical treatment of valvular atrial fibrillation influences the survival of patients.